2002
DOI: 10.1051/0004-6361:20011780
|View full text |Cite
|
Sign up to set email alerts
|

High resolution near-infrared spectro-imaging of NGC 7027

Abstract: Abstract. We present near-infrared spectro-imaging of the young planetary nebula NGC 7027 between 2.10 and 2.20 µm with high spatial (0.5 ) and high spectral (8.7 km s −1 ) resolution. The observations, made using BEAR at the CFHT, reveal the detailed morphology and kinematics of the ionized nebula (in the Brγ line and 16 other atomic lines) and the surrounding molecular envelope (in the 1-0 S(1) line of H2). The observations show that the ionized gas forms an elongated (∼6 × 12 , PA = 32• ), limb-brightened s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
116
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(132 citation statements)
references
References 29 publications
16
116
0
Order By: Relevance
“…7). Indeed, the morphology of high-velocity Br emission is very similar to that of the X-ray emission (Cox et al 2002). Similarly, both the optical emission and the diffuse soft X-ray emission from NGC 6543 appear to be point-symmetric (see Fig.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…7). Indeed, the morphology of high-velocity Br emission is very similar to that of the X-ray emission (Cox et al 2002). Similarly, both the optical emission and the diffuse soft X-ray emission from NGC 6543 appear to be point-symmetric (see Fig.…”
Section: Discussionmentioning
confidence: 58%
“…1 of KVS01). Emission from the X-rayemitting '' lobe '' projected northwest of the central star-a direction corresponding to blueshifted atomic and molecular gas (Cox et al 2002)-dominates the nebula in both the soft-and medium-band images. In the hard-band image, the emission is more balanced between the northwest (forwardfacing) and southeast (rearward-facing) X-ray lobes, and the northwest X-ray lobe has a smaller opening angle than in the medium-band image.…”
Section: No 2 2002 Extended X-ray Emission From Pnementioning
confidence: 99%
“…Indeed, Kwok et al (2008) found excellent agreement between a narrowband H 2 image of NGC 6583 and the Spitzer IRAC band 4 image while demonstrating the bipolar (double-coned) morphology of NGC 6583. Another dramatic case where H 2 emission unambiguously identifies bipolar morphology not necessarily evident in optical emission lines can be seen in the velocity integrated H 2 image of NGC 7027 (Cox et al 2002).…”
Section: Gatley's Rule and Mid-infrared Imagingmentioning
confidence: 95%
“…Note that the derived expansion velocity values are very different from those for the CO shell or photo-dissociation region. The CO or photo-dissociation emissions are prominent mostly along the bipolar axis (Fong et al, 2006;Cox et al, 2002). The kinematics of the major axis or the overall geometry involving the outer halo molecular zone is beyond the present study.…”
Section: Line Profile and Shell Expansion Velocitymentioning
confidence: 84%
“…For example, Baines et al (2003) (Walsh et al, 1997), and 212 km s −1 (Ershov and Berulis, 1989). Fong et al (2006) derived the expansion velocity of 13-16 km s −1 in the CO shell, while Cox et al (2002) found an evidence of 55 km s −1 from the line widths in the photo-dissociation region along the bipolar axis. Such results derived by the earlier studies seem to disobey the general law for lines formed near the central star, such as [ArIV]: such high excitation lines usually march out slowly but those emitted in the outer zones, such as [N II], expand swiftly.…”
Section: Introductionmentioning
confidence: 99%